2013
DOI: 10.1682/jrrd.2012.04.0062
|View full text |Cite
|
Sign up to set email alerts
|

Load applied on bone-anchored transfemoral prosthesis: Characterization of a prosthesis� A pilot study

Abstract: Abstract-The objectives of this study were to (1) record the inner-prosthesis loading during activities of daily living (ADLs), (2) present a set of variables comparing loading data, and (3) provide an example of characterization of two prostheses. The load was measured at 200 Hz using a multi-axial transducer mounted between the residuum and the knee of an individual with unilateral transfemoral amputation fitted with a bone-anchored prosthesis. The load was measured while using two different prosthetic knees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 48 publications
(81 reference statements)
2
72
0
Order By: Relevance
“…The magnitudes of the site‐specific load varied between the different patients evaluated in this study, most probably due to their individual anatomy, mass, amputation height, and walking pattern. The load magnitudes and variability agree well with previously published data on the loads applied to the femur or to the implant system during straight‐line level walking . It has further been shown that the walking pattern, pelvic tilt and hip extension change towards normal gait, as compared to gait using a socket prosthesis, when evaluating the same patients pre‐operatively and at a 2‐year follow‐up after treatment with an osseointegrated amputation prosthesis .…”
Section: Discussionsupporting
confidence: 86%
“…The magnitudes of the site‐specific load varied between the different patients evaluated in this study, most probably due to their individual anatomy, mass, amputation height, and walking pattern. The load magnitudes and variability agree well with previously published data on the loads applied to the femur or to the implant system during straight‐line level walking . It has further been shown that the walking pattern, pelvic tilt and hip extension change towards normal gait, as compared to gait using a socket prosthesis, when evaluating the same patients pre‐operatively and at a 2‐year follow‐up after treatment with an osseointegrated amputation prosthesis .…”
Section: Discussionsupporting
confidence: 86%
“…For the Ext/Flex moment during swing, the RSME% of 16 (14-24) for Total Knee were significantly lower compared to 35 (32)(33)(34)(35)(36)(37)(38) for Mauch Knee (p = 0.0356) and 41 (37-46) for C-Leg (p = 0.0330). Similarly, for the Add/Abd moment during swing, the RSME% of 16 (15)(16)(17)(18)(19)(20)(21)(22) for Total Knee were significantly lower compared to 29 (28)(29)(30) for Mauch Knee (p = 0.0318) and 19 (18)(19)(20) for C-Leg (p = 0.0344). For the Int/Ext moment during swing, the RSME% of 25 (20)(21)(22)(23)(24)(25)(26)(27) for Total Knee were lower than 39 (29-48) for C-Leg but not significantly (p = 0.0874).…”
Section: Resultsmentioning
confidence: 90%
“…Typically, quantitative assessments of prostheses performances rely on spatio-temporal, kinematic and kinetic gait characteristics [1][2][3][4][5][6]. In particular, the analysis of lower limb joints kinetics (i.e., forces, moments, power) has become critical to compare mechanical performances between adaptive dissipation prosthetic knee units [7][8][9][10][11][12][13][14][15][16][17][18][19] and an anatomical knee joint [2,3,20]. Furthermore, the development of osseointegrated fixations for bone-anchored prostheses requires a better understanding and monitoring of implant and prosthetic loading during locomotion to increase walking abilities (e.g., speed of walking) while assuring safety (e.g., limitation of high loading, fall prevention, breakage of fixation parts) [6,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Bone-anchored prostheses improve comfort and confidence of the users (Hagberg et al, 2008; Lundberg et al, 2011; Witso et al, 2006) and permit easier donning and doffing of the prosthesis (Jonsson et al, 2011). In addition, bone-anchored prostheses improve perception of prosthesis loading, defined as osseoperception (Haggstrom et al, 2013a; Jacobs et al, 2000; Lundborg et al, 2006), lead to fewer clinical visits to the prosthetist (Haggstrom et al, 2013b), and result in improvement of walking mechanics (Frossard et al, 2013; Hagberg et al, 2005; Tranberg et al, 2011). …”
Section: Introductionmentioning
confidence: 99%